PENENTUAN KEUNTUNGAN MAKSIMUM PADA PENJUALAN OLAHAN TAPE DENGAN MENGGUNAKAN METODE LAGRANGE (Studi Kasus: UD. Sari Madu) - ASTITI, FEMY AYU; ASIH, NI MADE; WIDANA, I NYOMAN (E-Jurnal Matematika; Vol 2 No 1 (2013): E-Jurnal MatematikaDO - 10.24843/MTK.2013.v02.i01.p023, 2013)
Optimization problems can be solved by various methods, such as Lagrange Method.   This  method can be used to find the solution. Using Lagrange method, the extreme value can be obtained, so that the optimal solution can be found. In this research, the maximum revenue of UD. Sari Madu is a limited by several constraints. After the objective function and constraint function being model, than maximum revenue is found. From first until fourth quarterly, the maximum revenue is found Rp. 9.701.333, Rp. 10.064.148, 9.793.272 and Rp. 9.397.730 respectively.
Keywords: Lagrange Method, Ekstrem Value, Optimization